The matriarch rules : how to own your power, know your worth, and lead the life you've always wanted - Patterson, Randy, 1967- (John Wiley & Sons, Inc., 2019)
Achieve success by becoming the change maker you were always meant to be. What is a matriarch' For one thing, you can tell she's in charge the second she walks into a room. She's bold, she's fierce, and she's got her own unique style. The matriarch isn't some crusty old lady dressed head-to-toe in black who sits at the head of the table barking demands at Sunday dinner. The modern matriarch is alive and vivacious. She's purposeful and deliberate about everything, from her career, to her home, to her family, to what she eats for lunch. She is not second guessing herself but moving herself and those she loves boldly into the future. The matriarch's vision for her career is as big as her love for her family, and she's paid her worth for work she's passionate about. The matriarch knows exactly what she wants the end game to be and she has the power to make it come to fruition. Simply put: she has her act together and you feel safer and more secure when you're in her presence. So, the question is, how does one become her' This book answers that question and more. - Recast yourself - Own your wins - Define your legacy - Leverage your success Written by the CEO of a multimillion-dollar startup, The Matriarch Rules provides you with guidelines that empower you to find personal success and growth in being the compassionate, powerful, and forward-thinking woman you are.